THE INFLUENCE OF THE MANAGER’S ROLE ON PERFORMANCE (Case Study on Micro, Small and Medium Enterprises Assisted by the WestJava Chamber of Commerce and Industry in Bandung) - Hendiarto, R Susanto; Erlangga, Kelvin; Santika, Wildan Permana; N, Christian M.E. Tofri; Kosmawan, Erlangga Tri Ramadhan; Apriliani, Reni (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the effect of the manager's role on the performance of Micro, Smalland Medium Enterprises (MSMEs) assisted by the West Java Chamber of Commerce and Industry (Kadin Jabar) in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 32 SMEs respondents. The variables studied from each respondent are the role of managers and performance. The type of data collected is primary data. The results of the study identify that the role of managers has a significant effect on performance. The object of this research is the sample of respondents used which is still limited to SMEs assisted by the West Java Chamber of Commerce in Bandung, therefore it is necessary to do further research based on more varied sampling with a longer duration, so that generalizable results are obtained.